Economics of crime and enforcement - Yezer, Anthony (Routledge, Taylor & Francis Group, 2025)
Assuming only a previous course in basic microeconomics, Economics of Crime and Enforcement is an innovative book which is strongly linked to the new theoretical and empirical journal literature.Showing the power of microeconomics in action, Yezer covers a wide array of topics, including benefit-cost and the imprisonment decision, enforcement games, juvenile crime, private enforcement, economics of three-strikes law, broken windows strategies, police profiling, crime in developing countries, as well as guns, drugs, and capital punishment. This second edition has been fully updated to reflect the latest developments in the field and features new chapters on behavioral economics and crime and crime and large cities. Problem questions provided at the end of each chapter allow students to reinforce their microeconomics skills and gain insight into the way they can be applied to case and application examples.Teaching resources, including PowerPoint slides and answers to problem questions, provide further support for instructors delivering courses on the economics of crime in a variety of settings.